Islamic Religious Education Curriculum Development Based On Multiculturalism in Merdeka Curriculum At Elementary School - Zuri Pamuji; Kholid Mawardi (Yayasan Nurul Yakin Bunga Tanjung, 2023)
Merdeka curriculum provides an opportunity for every teacher to express their creativity and ideas in curriculum development efforts, including Islamic Religious Education (PAI) teachers at the elementary school level. One of them is an adequate response to the existence of multiculturalism in social life which is sunatullah. This study aimed to discover the implementation pattern of multiculturalism-based Islamic Religious Education (PAI) curriculum development in the Merdeka curriculum and its relationship with the teacher's role as a curriculum developer, especially at the elementary school level. This research is based on a literature study using a descriptive-qualitative method aimed at collecting data through documentation techniques, both in printed and electronic form. The data analysis was carried out in three stages: editing, organizing, finding, and conducting further analysis. The results of the study show that a multicultural-based curriculum development pattern can be carried out in the Islamic Religious Education teaching module in the Merdeka curriculum, especially in the sections: learning objectives, Pancasila student profiles, apperception, and triggering questions, learning methods and activities, assessment instruments, reflection, and enrichment techniques. Multicultural values ​​that can be included as content in curriculum development include tolerance, equality, justice, and democracy (freedom). The development is carried out by incorporating the value of multiculturalism, which includes: equality, justice, democracy (freedom), and tolerance.